Passing the torch : planning for the next generation of leaders in public service - Besel, Karl (University of Arkansas Press, 2016)
Public-service executives, both elected and appointed within the public and nonprofit sectors, are retiring at record levels, and the number of Americans reaching age sixty-five annually will continue to rise over the next decade and is expected to surpass four million in 2020. Finding qualified, motivated leaders to fill vital public-service positions will challenge the public and nonprofit sectors. Unfortunately, recent studies show that few proactive steps are being taken by public-service organizations to plan for the next generation. Passing the Torch: Planning for the Next Generation of Public-Service Leaders provides an outline for those who will be facing and managing these looming changes. In this valuable guide, the factors that influence selection of a career in public service are explored through the authors years of experience as leaders in public-service organizations and through interviews with other public-service professionals. Passing the Torch will be essential for leaders of nonprofit organizations, university faculty, researchers in the field of nonprofit management, and students in nonprofit management courses.